Doppler ultrasound measurements of renal functional reserve in healthy subjects - Pekkafalı, Mehmet Zekai; Kara, Kemal (Medical ultrasonography, 2015)
The aim of this study was to calculate the normal values of renal functional reserve in healthy individuals measuring the resistive index and pulsatility index using Doppler ultrasonography. Forty healthy volunteer adults were included in the study. Their basal resistive index and pulsatility index values were measured and after oral protein load at 30th, 75th and 120th minutes, resistive index and pulsatility index measurements were repeated. The maximum changes in resistive index and pulsatility index from baseline were calculated in each subject which represented the renal functional reserve. The mean values of resistive index and pulsatility index decreased significantly starting with 30 minutes and consecutively at 75 and 120 minutes (for all p<0.05). The highest decrease compared to baseline values was recorded at 75 minutes and renal functional reserve values were calculated as 22.2% for resistive index and 25.4% for pulsatility index. Renal functional reserve can be calculated through Doppler resistive index and pulsatility index measures. We consider that it may be helpful to know normal values of renal functional reserve in healthy subjects.